Charcotiana and Amundsenia, two new genera in Teloschistaceae (lichenized Ascomycota, subfamily Xanthorioideae) hosting two new species from continental Antarctica, and Austroplaca frigida, a new name for a continental Antarctic species - Sochting, Ulrik; Garrido Benavent, Isaac; Seppelt, Rod; Perez Ortega, Sergio; De Los Rios Murillo, Asuncion; Sancho, Leopoldo Garcia; Froden, Patrik; Arup, Ulf; CASTELLO, Miris (The Lichenologist, 2014)
Based on a combined three locus analysis two new genera, Charcotiana and Amundsenia, are proposed in the lichen family Teloschistaceae, subfamily Xanthorioideae. Charcotiana includes the new species C. antarctica, which is known only from continental Antarctica. The bipolar genus Amundsenia includes the new species A. austrocontinentalis, which is also known only from continental Antarctica, and the Arctic species Caloplaca approximata which is here combined into the new genus. The two new genera are phylogenetically distinct, but poor in morphological characters; the new species consist mainly of minute apothecia in cracks of rocks located in the climatically harshest regions of the Antarctic. They are somewhat similar to another continental Antarctic species, Austroplaca frigida, which is described as a new name based on the illegitimate name Caloplaca frigida Søchting. The distribution of the four species is mapped.